(untitled) (Eurasian Journal of Ecology, 2026)
This article examines the multi-year (2014–2023) changes in mineralization and the ionic-salt composition of one of Kazakhstan’s most important reclamation structures the Tasotkel Reservoir on the Shu River. This reservoir serves as a primary water supply source for agriculture in the Shu and Moiynkum districts of the Zhambyl region and is used for irrigating 42.1 thousand hectares of land. The study analyzes the impact of the main tributaries (Karabalta, Aksu, and Toktas) on the formation of the reservoir’s chemical composition. Between 2014 and 2023, the mineralization of the Tasotkel Reservoir varied within 289,3–714,2, averaging (556,9±11,0) mg/dm³, which is not significantly different from the average mineralization of the upper section of the Shu River (541,5±14,0) mg/dm³. However, the high mineralization of the Karabalta (1316,9±51,0), Aksu (773,4±16,8), and Toktas (1050,0±38,0) rivers did not have a significant impact on the overall salinity of the reservoir. Throughout all seasons except autumn, the reservoir water was of a carbonate-calcium composition. During autumn, according to Alekin O.A.’s classification, the water belonged to the sulfate class and the magnesium or sodium group of the second type. During this period, MgSO₄ and Na₂SO₄ salts predominated, which was linked to the influence of the tributaries. In the lower reaches of the Shu River (near Konaev settlement), an increase in water mineralization by 80,1±13,4 mg/dm³ was recorded compared to the upper section. Over the last three years (2021–2023), the average annual mineralization of the Sarykau (1204,6±54,7), Karabalta (1396,9±60,2), Aksu (812,3±23,2), and Toktas (1153,8±58,9) rivers was higher compared to previous years: Sarykau (1114,0±203,4), Karabalta (1176,9±86,8), Aksu (725,2±21,2), and Toktas (925,0±49,5), respectively. The relatively low mineralization of the Tasotkel Reservoir water (less than 1 g/dm³) and the predominance of calcium bicarbonate have a beneficial reclamation effect on the saline and alkaline soils of the study area. However, using water from the Karabalta, Toktas, and Shu rivers for irrigation or technical purposes may lead to the formation of solid calcium carbonate and calcium sulfate salts. The likelihood of intensive precipitation of carbonate and sulfate salts increases when the water is heated, potentially leading to scale formation and clogging of technical equipment. Keywords: Tasotkel, mineralization, ionic-salt composition, hydrochemistry, water chemical composition formation, ecology